2016
DOI: 10.1002/jsfa.7646
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on triacylglycerol species in seed oil from high stearic sunflower lines with different genetic backgrounds

Abstract: BACKGROUND This study characterized the influence of temperature during grain filling on the saturated fatty acid distribution in triacylglycerol molecules from high stearic sunflower lines with different genetic backgrounds. Two growth chamber experiments were conducted with day/night temperatures of 16/16, 26/16, 26/26 and 32/26 °C. RESULTS In all genotypes, independently of the genetic background, higher temperatures increased palmitic and oleic acid and reduced linoleic acid concentrations. Increasing nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…Moreover, this trend showed differences in magnitude according to the genetic background or the high oleic mutation. This is in agreement with the general trend described by several authors working with different high oleic sunflower genotypes carrying the Pervenets mutation …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, this trend showed differences in magnitude according to the genetic background or the high oleic mutation. This is in agreement with the general trend described by several authors working with different high oleic sunflower genotypes carrying the Pervenets mutation …”
Section: Discussionsupporting
confidence: 93%
“…This accelerated but defective development is also reflected in the oil accumulation stage, which occurs between 14 DPA and 21 DPA under CO, but between 7 and 14 DPA under HS (Figure 3; Table 1). In line with our observations in C. sativa, decreased seed set, seed filling, and quality were also reported in oil seed crops such as Brasicca napus, soybean, and sunflower (Faraji et al, 2009;Izquierdo et al, 2016;Nakagawa et al, 2020;Staniak et al, 2021;Mácová et al, 2022).…”
Section: Heat Stress Causes Accelerated and Altered Seed Development ...supporting
confidence: 89%
“…Floral development and seed yield are strongly affected by temperature, with milder temperatures resulting in higher yields (Krzyzȧniak et al, 2019;Zanetti et al, 2021). Furthermore, camelina accessions and cultivars grow in varying climatic niches throughout the globe, and temperature was found to elicit plasticity in seed oil in camelina (Brock et al, 2020) and other oil seed crops (Izquierdo et al, 2016;Xu et al, 2016;Alsajri et al, 2020;Nakagawa et al, 2020). C. sativa includes spring and winter biotypes, with spring biotypes being the most studied thus far since winter biotypes required vernalization for flowering (Anderson et al, 2018;Malik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This might be a reason for the higher oil contents in September for the Ain oussera and Laghouat regions. Similar to the results found in this study, Izquierdo et al [43] have suggested that the TAG biosynthesis increases considerably at lower temperatures. The oil accumulation is also affected by environmental factors other than the temperature: day length and light exposure, which vary with the season (Table 1).…”
supporting
confidence: 92%